Dental arch morphology in normal occlusions - Luiz Renato Paranhos; Will A. Andrews; Renata Pilli Jóias; Fausto Bérzin; Eduardo Daruge Júnior; Tarcila Triviño (Universidade Estadual de Campinas, 2015)
Aim: The aim of this study was to identify the prevalence of 3 different mandibular dental arch morphologies in individuals with natural normal occlusion. Methods: Fifty-one mandibular dental casts of Caucasian individuals with natural normal occlusion were digitized. Each was without a history of orthodontic treatment and presenting at least four of the six keys to normal occlusion described by Andrews. Twelve orthodontists evaluated the prevalence of the square, oval and tapered arch shapes by analyzing the mandibular digital images. Results: The most prevalent dental arch shape was oval (41%), followed by square (39%), and tapered (20%) shapes. Conclusions: During leveling and alignment phases, when elastic-alloy-wires are greatly used, the orthodontist could use any of the studied arch shapes (oval, square, tapered), once the prevalence of all of them was similar.